Electric Power Weeder Innovation and Improvement (International Journal of Innovative Research in Engineering & Management, 2021)
This article shows the design, production, analysis, control,  and experimental activities in which is considered to be a  suitable engineering education. The design for a motor powered weeder is performed for home gardening labour has  been detailed. In India over the last 20 years, labour saving  and efficiency have been required since the involvement in  agricultural industry was reduced to 50 percent. An electric  powered weeder design is developed because this is  concerned with environment, agriculture, and engineering.  Design and manufacturing is the core to engineering,  education for mechanical engineering requires the concept of  practical design and manufacturing. The initial aim is the  development and manufacturing of a weeder via a rotating  body and the mechanical component that nails up and down.  The second is stress analysis and control experimental  validation of the weeder.
Keywords: Agriculture; Blades; Engineering; Production; Weeding